Desarrollo de una propuesta para la producción de biogás en un reactor anaerobio de lecho estructurado (ASTBR) para la vereda Calderón, Puerto Boyacá (2020)
The purpose of this work was to develop a proposal to produce biogas from domestic wastewater and organic solid wastes, working with the Antonio Nariño University and the International Gas Transporter (TGI) company, through the use of a ASTBR bench scale reactor, with a total volume of 70L for the “El Prado Educational Institution”, located in the Vereda Calderón, Puerto Boyacá. To accomplish this, we started using the experimental data obtained by the construction and operation of 2 laboratory-scale ASTBR reactors with low-cost materials, with an effective volume of 2.5 L, each one with a median biogas production of 0.83NL/d, employing a synthetic wastewater feed at a concentration in terms of COD, of 735.97 mgO2/L, with a removal percentage of organic matter of 37.01%. Subsequently, based on the results obtained from the laboratory scale, the sizing was carried out using the principle of geometric and kinematic similarity, thus obtaining an effective volume of 55.57L, and a biogas production of 26.44L/d. Finally, the costs of the proposal for the Vereda Calderón were estimated on $37,752,397 COP for the first year of operation, from the second year of operation onwards, there will be a total cost reduction of 34.11%, on the other hand, the cost per kWh is $2,673.17 COP/kWh for the biogas production process at the El Prado Educational Institution